Pedagogical innovations in sustainable development: Fair trade in the classroom - Lewis, Katrina; Dickinson, Torry; Lewis, Summer (Kansas State University, 2009)
The educators introduce students to basic concepts and practices of sustainable development by exploring fair trade in the world today. They guide students in researching, creating, and implementing fair trade projects in different disciplinary contexts and help students understand fair trade practices as a part of sustainable development. When fair trade works best, it develops equal, long-term relationships between producers and consumers in the world, encourages ecologically-friendly production, transparent gender and ethnic-inclusive business practices, facilitates the emergence of long-term networks of cooperatives that practice democratic decision making, and creates new economic power bases in the global South with support from equitable trading partners in the global North. Fair trade is part of sustainable development because fair trade practice represents an innovation in ecological, economic, political, and social relations. These new regional-to-global linkages are designed to provide long-term stability for the world’s people and environment. In their respective fields, the educators define sustainable development holistically, involving ecological, social, cultural, economic, and political relationships. Promoting sustainability involves the conservation and re-use of natural resources in addition to the generation of long-term, socio-economic ways of living that restore ecosystems and global human relationships. This is a departure from traditional definitions of sustainability; the educators’ pedagogical perspective moves beyond the physical realm to incorporate the development of social relations between people. Defined in this way, sustainability is an integral component in the educators’ disciplines. As presenters at the Conference, the educators will describe how they integrate fair trade education into their fields and programs. These include Interior Architecture and Product Design, Women’s Studies, Nonviolence Studies, the Campaign for Nonviolence, and the KSU Fair Trade Week and Marketplace. In Interior Architecture and Product Design, the educator works with students on conceptual designs for a fair trade cooperative in La Esperanza, Nicaragua. This project engages students in activities on and off campus, exposing students to the wide range of issues relating to sustainability and fair trade. In Women’s Studies, another educator introduces students to active learning via academic readings and volunteer work with the KSU Fair Trade Week. Students design and sell fair trade t-shirts that are obtained from U.S. based fair trade groups that work with women-owned cooperatives in Mexico and Nicaragua. By teaching nonviolence studies, this educator helps students develop an awareness of workplace exploitation in the U.S. and other countries, and to understand how alternative relations are established. In addition, the educator works with the Campaign for Nonviolence, Nonviolence Studies, and Women’s Studies to initiate learning experiences in Central America that will enable the student organization “Engineers Beyond Borders” (as supervised by Civil Engineer David Chandler) to design renewable energy systems, using solar, water, and wind power for fair trade cooperatives and their workplace production. Another educator will discuss her fair trade and sustainability experience as a KSU undergraduate, international volunteer, worker-owner in a U.S. fair trade cooperative, U.S. marketing coordinator for a Guatemalan woman's textile cooperative, author, researcher, and educator.
Keywords: Fair trade; Sustainable development; Teaching